Modelo de televisión comunitaria para el desarrollo humano: estudio de la televisión comunitaria de Colombia y nueva propuesta de programación para su audiencia (2013)
This paper provides the concepts for building a community television model for human development, that from programming, projection, strategic alliances, participation and human development, helps to encourage people’s expressive capabilities and to improve their life standards; and also becomes the input for the design of programming that, from the topics of coexistence, democracy and citizenship, children and youth and community experiences, helps to meet the country’s development needs.